Environmental Education Study Projects for College Students - Wert, Jonathan M.; Tennessee Valley Authority, Knoxville ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This publication concerns three environmental education study projects designed to help the college instructor, student, or group of students in identifying environmental problems at the community level and helping to find solutions to them. It discusses the need for and use of environmental problem solving and includes some factors involved with this method. The projects are concerned with three topics: (1) identifying and lessening the impact of an environmental problem in the community, (2) assessing the impact of a development project, and (3) doing scientific environmental research. Each project discussion includes a methods section, questions for consideration, and data organization. At the end of the publication is a community survey instrument for determining environmental concerns. (Author/MA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Decision Making Skills; Educational Resources; Environmental Education; Higher Education; Instructional Materials; Interdisciplinary Approach; Learning Activities; Problem Solving; Resource Materials; Student Projects; Guides, General